Ewa Godlewska, Polityka etniczna Republiki Austrii, Wydawnictwo Uniwersytetu Marii Curie-Skłodowskiej, Lublin 2021, ss. 352. - Romejko, Adam (Studia Gdańskie, 2022)
Ewa Godlewska, Polityka etniczna Republiki Austrii, Wydawnictwo Uniwersytetu Marii Curie-Skłodowskiej, Lublin 2021, ss. 352.